Prediction of Meta-Skills Based on Metcognition - Jodion Siburian; Lely Mardiyanti (Jurnal Penelitian Pendidikan IPA, 2023)
Meta-skills and metacognition are 21st century skills. The correlation between metacognition and meta-skills has never been studied before. Even though both have a relationship based on concept studies. Therefore, this study aims to predict the extent to which metacognition can influence meta-skills. This quantitative research is correlational research conducted on 30 undergraduate students of Biology Education, Universitas Jambi. Students' metacognition was measured using a test. Students' meta-skills were measured using a questionnaire whose scores were transformed into interval data. The results were analyzed using simple linear regression. The results of data analysis showed there is a correlation between students' metacognition and meta-skills (p = < 0.01). There is a significant regression equation [F (1. 58) = 14.28, p < 0.01] with an R2 of 0.20. Students' meta-skills can be predicted using the regression equation y = 33.63 + 0.46x. The regression coefficient (B = 0.46) indicates that an increase in metacognition score by 1 number will increase students' meta-skills score by 0.46.